Investigation Policy on Crime of Unfair Business Competition After the Enforcement of the Omnibus Law - Zubairi Zubairi (Universitas Negeri Semarang, 2021)
Violations of Law 5/1999 may be subject to administrative and criminal sanctions. Administrative sanctions are imposed by KPPU, while for criminal sanctions it is not clear by whom. The legal problem is how are the investigation arrangements in Law 5/1999 in conjunction with Law 11/2020? and What is the investigation policy in the RUU Monopoly Practices?. This is a legal research with statute and conceptual approach. Primary and secondary sources were collected using the literature search and analyzed using a prescriptive method. The institution authorized to conduct investigations in Law 5/1999 in conjunction with Law 11/2020 is not clearly regulated whether from the Police or PPNS, in addition, legal subjects that can be investigated are not clearly regulated. Likewise, RUU Monopoly Practices does not improve the investigation arrangements. The only investigation setting is only in Article 39 paragraph (2) of the Monopoly Practices Bill which stipulates that KPPU in conducting searches and/or confiscations may request assistance from Polri and is not given other powers. Whereas RUU Monopoly Practices, but it is not clear how the investigation will be carried out. Suggestions for solving these legal problems are that Law 5/1999 needs to improve the investigation arrangements. Should be in English, maximum 250 words, contain the background of research, facts, research problems, method, findings, suggestions.